2022
DOI: 10.1111/wrr.13044
|View full text |Cite
|
Sign up to set email alerts
|

Robbing Peter to Pay Paul: Chlorhexidine gluconate demonstrates short‐term efficacy and long‐term cytotoxicity

Abstract: Wound cleansing agents are routine in wound care and preoperative preparation.Antiseptic activity intends to prevent contaminating microbes from establishing an infection while also raising concerns of cytotoxicity and delayed wound healing. We evaluated the cytotoxicity of five clinically used wound cleaning agents (saline, povidone iodine, Dove ® and Dial ® soaps, and chlorhexidine gluconate [CHG]) using both an ex vivo and in vivo human skin xenograft mouse model, in contrast to classical in vitro models th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
(121 reference statements)
1
6
0
2
Order By: Relevance
“…These results are consistent with our previous study, which demonstrated the lack of the cytotoxicity effect of modified HA combined with MGTN on the 3D model of the gingival tissue equivalent (Munar-Bestard et al; Mangostanin hyaluronic acid hydrogel as an effective biocompatible alternative to chlorhexidine, 2023; manuscript submitted for publication). In addition, in the commercial 3D model of oral mucosa epithelium, the treatment with HA 0.05% MGTN gel showed low IL-1α levels, contrary to the positive control or to the gels containing CHX, thus showing excellent biocompatibility with tissues, as observed for the Betadine and Prontosan gels, whereas Crystalmina gel that contains 1% CHX exhibited a higher cytotoxicity, in concordance with the literature. The lack of effect in cell viability induced by the positive control on the 3D model of human epidermis can be explained by the keratinized external layer of this tissue and/or to the relatively low SDS concentration used in this assay, evidencing the low sensibility of the 3D model of human epidermis tissue for MTT . In contrast, comparing the effects of HA with 0.05% MGTN with the commercial periodontal gels, we observed that the commercial periodontal gels containing 0.2% CHX exhibited a higher cytotoxicity in the 3D oral mucosa model, in line with CHX effects .…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with our previous study, which demonstrated the lack of the cytotoxicity effect of modified HA combined with MGTN on the 3D model of the gingival tissue equivalent (Munar-Bestard et al; Mangostanin hyaluronic acid hydrogel as an effective biocompatible alternative to chlorhexidine, 2023; manuscript submitted for publication). In addition, in the commercial 3D model of oral mucosa epithelium, the treatment with HA 0.05% MGTN gel showed low IL-1α levels, contrary to the positive control or to the gels containing CHX, thus showing excellent biocompatibility with tissues, as observed for the Betadine and Prontosan gels, whereas Crystalmina gel that contains 1% CHX exhibited a higher cytotoxicity, in concordance with the literature. The lack of effect in cell viability induced by the positive control on the 3D model of human epidermis can be explained by the keratinized external layer of this tissue and/or to the relatively low SDS concentration used in this assay, evidencing the low sensibility of the 3D model of human epidermis tissue for MTT . In contrast, comparing the effects of HA with 0.05% MGTN with the commercial periodontal gels, we observed that the commercial periodontal gels containing 0.2% CHX exhibited a higher cytotoxicity in the 3D oral mucosa model, in line with CHX effects .…”
Section: Discussionsupporting
confidence: 81%
“…Ao longo de 14 dias, observou-se um aumento gradual da citotoxicidade, nas extremidades da ferida houve redução da viabilidade celular na camada de epiderme e derme, progredindo acentuadamente e afetando uma parte maior do tecido. Mesmo após o enxague do CHG por 30 minutos, a capacidade prejudicial do CHG às células continua presente, resultando em uma deterioração profunda das células da ferida (Cheong et al, 2022).…”
Section: Base De Dados E Nº De Artigos Encontradosunclassified
“…As feridas foram criadas na pele enxertatada após 8 semanas do procedimento e tratadas com irrigação de CHG por 2 minutos durante 14 dias. Os resultados reafirmaram o comprometimento expressivo da renovação celular e distanciamento acentuado das bordas da ferida neopidérmica, replicando assim, os resultados observados no tratamento contínuo das feridas ex vivo (Cheong et al, 2022).…”
Section: Base De Dados E Nº De Artigos Encontradosunclassified
“…Chlorhexidine exhibits the highest level of cytotoxicity and is associated with increased antimicrobial efficacy soon after application, also persists over time for up to 14 days and inhibits wound healing in a human skin xenograft mouse model in vivo [33] . Chlorhexidine 2% is a medication widely used in dentistry, in endodontics it is used more as an irrigant than as an intraoral medication between appointments.…”
Section: Limitations and Cytotoxicitymentioning
confidence: 99%